Is radial extracorporeal shock wave therapy combined with a specific rehabilitation program (rESWT + RP) more effective than sham-rESWT + RP for acute hamstring muscle complex injury type 3b in athletes? Study protocol for a prospective, randomized, double-blind, sham-controlled single centre trial - Javier Crupnik; Santiago Silveti; Natalia Wajnstein; Alejandro Rolon; Alisa Vollhardt; Peter Stiller; Christoph Schmitz (Journal of Orthopaedic Surgery and Research, 2019)
Abstract Background Acute injuries of the hamstring muscle complex (HMC) type 3b (interfascicle/bundle-tear) are frequently observed in various sports disciplines both in elite and recreational sport. The treatment of choice of acute HMC injuries type 3b is a progressive physiotherapeutic exercise programme. Besides this, there is currently only insufficient scientific evidence to support other treatment methods, including local infiltrations and injections of platelet-rich-plasma. Very recently, it was demonstrated that extracorporeal shock wave therapy (ESWT) may accelerate regeneration after acute skeletal muscle injury. The aim of the present study is to test the hypothesis that the combination of radial ESWT (rESWT) and a specific rehabilitation program (RP) is effective and safe in treatment of acute HMC injury type 3b in athletes, and is statistically significantly more effective than the combination of sham-rESWT and RP. Methods We will perform a double blind, randomized, sham-controlled clinical trial at the clinic KinEf Kinesiología Deportiva, Ciudad Autónoma de Buenos Aires, Argentina. Forty patients with acute HMC injury type 3b will be randomly allocated to receive either rESWT (nine rESWT sessions; three sessions per week; 2500 radial extracorporeal shock waves (rESWs) per session; energy density depending on what the patient tolerates) or sham-rESWT. In addition, all patients will receive a specific rehabilitation program that will last for 8 weeks. The primary outcome measure will be the individual time (days) necessary to return to play. Secondary outcomes will include the presence or absence of reinjury during a time period of 6 months after inclusion into the study. Discussion Because of the lack of adequate treatment options for acute HMC injury type 3b in athletes and particularly the high reinjury rate, we hypothesize that the results of this trial will be of importance and have impact on clinical practice. Trial registration ClinicalTrials.gov ID NCT03473899. Registered March 22, 2018.